The utility of Desmidiospora: a paradigm shift based on Paleogene fungal remains from the Ñirihuau Basin, Argentina. (1st October 2020) - Bianchinotti, M. Virginia; Martínez, Marcelo A.; Cornou, M. Elina
Abstract: Fungal remains similar to those described as Desmidiospora willoughbyi were found in samples from the Río Foyel section (El Foyel Group of Paleogene age), Ñirihuau Basin, Argentina. A full description and illustrations are presented. The names D. willoughbyi and D. marginiconvoluta as defined are shown to be inadequate. The history of the names and actual affinity of taxa presently assigned to those names are discussed. Arguments against the use of Desmidiospora for fungal remains other than the conidia of an entomopathogenic species are presented. Instead, the lobulate fossil remains should be treated as germlings or immature ascomata from epiphyllous fungi of polyphyletic origin.